THE ARC DE TRIOMPHE TO THE LOUVRE TO VERSAILLES (EXPERIENCE OF SPATIAL CITY BID) (Municipal economy of cities. Series: «Economy science», 2013)
Studied the role of the spatial axis and arches in the development of structure of the historical city.